The quiescent center and the stem cell niche in the adventitious roots of Arabidopsis thaliana. (3rd May 2016) - Della Rovere, Federica; Fattorini, Laura; Ronzan, Marilena; Falasca, Giuseppina; Altamura, Maria Maddalena
ABSTRACT: Adventitious rooting is essential for the survival of numerous species from vascular cryptogams to monocots, and is required for successful micropropagation. The tissues involved in AR initiation may differ in planta and in in vitro systems. For example, in Arabidopsis thaliana, ARs originate from the hypocotyl pericycle in planta and the stem endodermis in in vitro cultured thin cell layers. The formation of adventitious roots (ARs) depends on numerous factors, among which the hormones, auxin, in particular. In both primary and lateral roots, growth depends on a functional stem cell niche in the apex, maintained by an active quiescent center (QC), and involving the expression of genes controlled by auxin and cytokinin. This review summarizes current knowledge about auxin and cytokinin control on genes involved in the definition and maintenance of QC, and stem cell niche, in the apex of Arabidopsis ARs in planta and in longitudinal thin cell layers.